2013
DOI: 10.1186/1471-2121-14-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-mediated internalization of Staphylococcus aureus does not require vinculin

Abstract: BackgroundDisease manifestations of Staphylococcus aureus are connected to the fibronectin (Fn)-binding capacity of these Gram-positive pathogens. Fn deposition on the surface of S. aureus allows engagement of α5β1 integrins and triggers uptake by host cells. For several integrin- and actin-associated cytoplasmic proteins, including FAK, Src, N-WASP, tensin and cortactin, a functional role during bacterial invasion has been demonstrated. As reorganization of the actin cytoskeleton is critical for bacterial ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…To date, various lines of evidence have demonstrated that the excessive activation of TGF‐β is associated with various disorders. On the other hand, it is well accepted that some bacteria utilize integrin cascade to invade into the cells (Pizarro‐Cerda and Cossart, ; Kim et al ., 2009; Borisova et al ., ). Based on our idea in the present study, these facts may suggest that bacteria or virulence factors that are capable of inducing actin rearrangements via integrin cascade promote the activation of TGF‐β from the ECM, leading to TGF‐β‐related diseases.…”
Section: Discussionmentioning
confidence: 97%
“…To date, various lines of evidence have demonstrated that the excessive activation of TGF‐β is associated with various disorders. On the other hand, it is well accepted that some bacteria utilize integrin cascade to invade into the cells (Pizarro‐Cerda and Cossart, ; Kim et al ., 2009; Borisova et al ., ). Based on our idea in the present study, these facts may suggest that bacteria or virulence factors that are capable of inducing actin rearrangements via integrin cascade promote the activation of TGF‐β from the ECM, leading to TGF‐β‐related diseases.…”
Section: Discussionmentioning
confidence: 97%
“…Upon phosphorylation by integrins, Src associates and activates FAK to regulate several actin-related processes, including phosphorylation of key substrates such as paxillin and cortactin 32 51 52 53 54 55 . It has also been shown that activation of host cell Src and FAK is correlated to the actin dependent internalization of bacterial pathogens 56 57 58 59 . The serine-threonine kinase, PAK, acts as an effector of Rac1 and other GTPases 60 61 and previous results from the author’s group demonstrate that cells expressing constitutively active Rac1 are more susceptible to EAs invasion 62 .…”
Section: Discussionmentioning
confidence: 99%
“…The contribution to S. aureus invasion of different integrin‐interacting proteins appears to differ in various cell types. For example, whereas focal adhesion kinase is essential for S. aureus invasion of fibroblasts, vinculin is dispensable (38, 39). Our data now establish that ILK is an indispensable component for staphylococcal internalization in epidermal keratinocytes and that it does not appreciably mediate at least a subset of TLR2‐mediated innate immunity responses to microbial pathogens.…”
Section: Discussionmentioning
confidence: 99%